2016
DOI: 10.1039/c6fo00095a
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effects of lycopene on liver enzymes involved in methionine and xenobiotic metabolism in hyperhomocysteinemic rats

Abstract: Hyperhomocysteinemia, defined by an increased plasma homocysteine level, is commonly associated with chronic liver diseases. A link between the elevated homocysteine level and oxidative stress has been demonstrated. Indeed the pathogenesis of liver diseases in the case of hyperhomocysteinemia could be due to this production of oxidative stress. Many studies have demonstrated the antioxidative properties of lycopene, a carotenoid. Therefore, the present study was designed to induce hyperhomocysteinemia in male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 43 publications
2
17
0
Order By: Relevance
“…This data is in accordance to Emami et al, 2016 , Piña-Zentella et al, 2016 , Agrawal and Singh, 2017 , Guo et al, 2018 . Increasing MDA during obesity is an indication for extensive lipid peroxidation, which plays a crucial part in oxidative stress development and may disturb the soundness of cellular membranes ( Mozos et al, 2017 , Yefsah-Idres et al, 2016 ). Administration of Moringa olifera seed oil extract and LYC perfectly ameliorated the obesity induced oxidative stress and promoted antioxidant reserve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This data is in accordance to Emami et al, 2016 , Piña-Zentella et al, 2016 , Agrawal and Singh, 2017 , Guo et al, 2018 . Increasing MDA during obesity is an indication for extensive lipid peroxidation, which plays a crucial part in oxidative stress development and may disturb the soundness of cellular membranes ( Mozos et al, 2017 , Yefsah-Idres et al, 2016 ). Administration of Moringa olifera seed oil extract and LYC perfectly ameliorated the obesity induced oxidative stress and promoted antioxidant reserve.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated liver and kidney enzymes were an expected result of increased MDA during obesity, which is an indicator for extensive lipid peroxidation. MDA plays a substantial role in oxidative stress and may disrupt the integrity of hepatic and renal cell membranes ( Mozos et al, 2017 , Yefsah-Idres et al, 2016 ), which causes leakage of their enzymes into blood. These changes were clear in histopathological sections and could be seen as hepatic vacuolar degeneration and multifocal to diffuse degeneration of renal tubular epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…It decreased the levels of ALT, serum homocysteine, and AST. In addition, its hepatoprotective effect was performed by enhancing the S-adenosyl-homocysteine hydrolase, hepatic cystathionine beta-synthase activities and decreasing the level of hepatic MDA [70]. Moreover, tomato powder has been shown to have a protective agent against alcohol-induced hepatic injury by inducing cytochrome p450 2E1 [80].…”
Section: Hepatoprotectivementioning
confidence: 99%
“…A recent study showed that lycopene exerted anti-inflammatory activities against paracetamol liver injury (APAP) in C57BL/6 mice by improving the redox state [147]. Yefsah-Idres et al [148] showed that rats with a diet high in methionine content had abnormal histological features accompanied by an increase in the levels of serum homocysteine, alanine aminotransferase (ALT), and aspartate aminotransferase (AST), as well as MDA hepatic and a decrease in the activities of cystathionine-β-synthase (CBS) and S-adenosyl-homocysteine hydrolase, indicating that lycopene supplementation reversed hyperhomocysteinemia (related to oxidative stress), providing additional evidence of the hepatoprotective effects of lycopene. Lycopene also showed beneficial effects against HCC by modulating cell proliferation, glycolysis, and ultrastructure of liver cells [149].…”
Section: Carotenoids and Hepatic Healthmentioning
confidence: 99%